0566 Innovative Methodology and Device Detecting Head Position for the Treatment of Obstructive Sleep Apnea and Snoring - Aghassi, Payam; Sailer, Stacia; Lyons, Christopher; Lawee, Michael (Sleep (New York, N.Y.), 2019)
Introduction Many individuals experience reduced AHI and SPO2 de-saturation with the torso in the non-supine position; however severity is still too high to consider it as an effective treatment option. In this clinical trial, we have discovered that if only the head position is considered, all subjects are positional sensitive and OSA severity can be calculated and consistently minimized by limiting the allowable range of head pitch and roll angle during sleep. Methods Ten subjects underwent a standard polysomnography with an additional head angle sensor and coached to fall asleep in various head positions. Head angles were achieved by propping pillows or verbal intercom requests to reposition the head. When possible, torso position was swapped between supine and non-supine for a given head roll angle epoch to prove that OSA severity did not change with torso position. Scoring was completed utilizing AASM guidelines. Each sleep epoch of unique head pitch and roll angle is scored individually for AHI and SPO2 de-saturation. Results Two subjects were eliminated for having no OSA. Six were female and 2 were male of the eight remaining subjects, ranging from 32 to 64 years of age and BMI ranging from 24 to 49. Three subjects were position sensitive with supine to non-supine AHI ratio >2, and the remaining experienced AHI ratio <1.6. Of the population, 86% experienced >70% improvement in AHI and SPO2 de-saturation and 14% observe a 34% improvement, with the head roll angles <20° from the horizon. There was no consistently observed correlation between subject gender, age, BMI, or torso position for the various head pitch and roll angles epochs. Conclusion Head position, independent of torso position can be used reliably to minimize AHI and SPO2 de-saturation. A treatment device enforcing safe head angles during sleep will be validated in phase II clinical trials. Support (If Any) Sleep Systems clinical trial was supported by UMass Medical School, Mass Lung and Allergy, UMass M2D2 and New England IRB.